Valley splitting of single-electron Si MOS quantum dots - Gamble, John King; Harvey-Collard, Patrick; Jacobson, N. Tobias; Baczewski, Andrew D.; Nielsen, Erik; Maurer, Leon; Montaño, Inès; Rudolph, Martin; Carroll, M. S.; Yang, C. H.; Rossi, A.; Dzurak, A. S.; et al. (Applied physics letters, 2016)
Silicon-based metal-oxide-semiconductor quantum dots are prominent candidates for high-fidelity, manufacturable qubits. Due to silicon's band structure, additional low-energy states persist in these devices, presenting both challenges and opportunities. Although the physics governing these valley states has been the subject of intense study, quantitative agreement between experiment and theory remains elusive. Here, we present data from an experiment probing the valley states of quantum dot devices and develop a theory that is in quantitative agreement with both this and a recently reported experiment. Through sampling millions of realistic cases of interface roughness, our method provides evidence that the valley physics between the two samples is essentially the same.